Atherogenicity of low-density lipoproteins after switching from a protease inhibitor to dolutegravir: a substudy of the NEAT022 study. (13th April 2022) - Saumoy, Maria; Sánchez-Quesada, Jose Luís; Assoumou, Lambert; Gatell, José Maria; González-Cordón, Ana; Guaraldi, Giovanni; Domingo, Pere; Giacomelli, Andrea; Connault, Jérôme; Katlama, Christine; Masiá, Mar; Ordónez-Llanos, Jordi; et al.
Abstract: Background: The aim of this study was to investigate whether switching from a ritonavir-boosted PI-based regimen to a dolutegravir-based regimen improved the atherogenic properties of LDL particles in patients with HIV. Methods: This was a substudy of the NEAT022 study (ClinicalTrials.gov NCT02098837). Adults with HIV with a Framingham score >10% or aged >50 years and being treated with a stable boosted PI-based regimen were randomized to either switch to dolutegravir or continue with boosted PI. At baseline and Week 48, we assessed atherogenic LDL properties: LDL particle size and phenotype (A, intermediate, B), oxidized LDL (ox-LDL) and lipoprotein-associated phospholipase A2 (Lp-PLA2) activity. Results: Eighty-six participants (dolutegravir 44; PI 42) were included. Participants had a median (IQR) age of 54 (51–57) years and 79.1% were male. In the dolutegravir arm, after 48 weeks, we observed: (1) an increase in LDL size [median 1.65 Å (IQR −0.60 to 4.20); P = 0.007], correlated with the decrease in triglyceride concentration [Spearman correlation = −0.352 ( P = 0.001)], with a corresponding decrease of subjects with atherogenic LDL phenotype B (36.4% to 20.5%; P = 0.039); (2) a decrease in Lp-PLA2 activity [median 1.39 μmol/min/mL (IQR −2.3 to 0.54); P = 0.002]; and (3) a decrease in ox-LDL [median 14 U/L (IQR −102 to 13); P = 0.006]. In the PI arm, none of these favourable lipid modifications was observed. Conclusions: Forty-eight weeks after switching from a PI-based to a dolutegravir-based regimen, patients with Framingham score >10% or aged >50 years showed improvement of several atherogenic lipid features, including LDL particle phenotype, ox-LDL and Lp-PLA2.